Potential of cash waqf for poverty alleviation in Malaysia: a system dynamics approach - Shahida Shahimi; Mohd Umar Mohd Marzuki; Zaini Embong (Penerbit Universiti Kebangsaan Malaysia, 2013)
Poverty alleviation has always been one of the top agendas in any country, including Malaysia. This is evidenced from the spending of the government for the purpose of uplifting the income of the poor. The objective of this paper is therefore to explore alternative tool in eradicating poverty, specifically in Malaysia, by exploring the role of cash waqf. This paper examines the potential impact of cash waqf on the Malaysian economy. Cash waqf is specifically analysed in this paper as an alternative instrument that can improve the overall social welfare system and reduce poverty rate; and at the same time, lessen the burden of the government. To analyse the potential of cash waqf model in a dynamic system, this study employs system dynamics methodology. The feedback nature of the whole system is modelled and outputs in the form of figures are derived from simulations. With two different cases (i.e. set of assumptions) under study, the model simulations show that cash waqf is significant in alleviating poverty by up to 50 per cent for both cases. Apart from that, government spending can also be significantly reduced. Total savings can go over RM13 billion or an average of RM433 million a year over 30 years. Given the findings, the government can take into account the potential of implementing cash waqf in Malaysia.